2020
DOI: 10.1111/jth.14839
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic acid promotes thrombus stability by inducing rapid formation of neutrophil extracellular traps: A new mechanism of thrombosis

Abstract: Background: Lysophosphatidic acid (LPA), a bioactive phospholipid released by activated platelets, can induce platelet shape changes and aggregation, which may play an important role in thrombosis. In contrast, the interaction of LPA with neutrophils in thrombosis has not been studied. Recently, neutrophil extracellular traps (NETs) have been shown to bind plasma proteins and activate platelets, which promotes thrombosis.Objectives: To investigate whether LPA could activate neutrophils to release NETs, predisp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 50 publications
3
23
0
Order By: Relevance
“…In a study by Jimenez et al histone levels were strongly associated with the degree of VTE and with mortality, as well as with C-reactive protein (CRP) and circulating leukocytes [ 147 ]. Similarly, in other studies on thrombotic diseases, a significant acceleration of intrapulmonary thrombus lysis by a combination of DNase and tPA has also been observed [ 146 ].…”
Section: Immunothrombosis Nets and Covidsupporting
confidence: 63%
See 1 more Smart Citation
“…In a study by Jimenez et al histone levels were strongly associated with the degree of VTE and with mortality, as well as with C-reactive protein (CRP) and circulating leukocytes [ 147 ]. Similarly, in other studies on thrombotic diseases, a significant acceleration of intrapulmonary thrombus lysis by a combination of DNase and tPA has also been observed [ 146 ].…”
Section: Immunothrombosis Nets and Covidsupporting
confidence: 63%
“…LPA is a bioactive phospholipid, released by activated platelets, that induces the release of NETs. These may, in turn, activate further platelets to release more LPA and perpetuate the LPA–NET–platelet positive feedback mechanism [ 145 , 146 ]. In a study by Jimenez et al histone levels were strongly associated with the degree of VTE and with mortality, as well as with C-reactive protein (CRP) and circulating leukocytes [ 147 ].…”
Section: Immunothrombosis Nets and Covidmentioning
confidence: 99%
“…The core proteins of NETs are H2A, H2B, H3, and H4, which account for about 70% of the total NET proteins, followed by NE, S100A8, lactotransferrin, azurocidin, and cathepsin G [16,17]. In addition, previous studies and our work also found that NETs also contain matrix metalloproteinase-9 (MMP-9), [18,19], tissue factor (TF) [20], von Willebrand factor (vWF), and fibrinogen [5,21].…”
Section: Structural Components Detection Andsupporting
confidence: 65%
“…Cardioembolic events account for up to 30% of all ischemic strokes [ 2 ]. Accurate gauging of thrombotic stability is critical, helping to guide therapy and procedural planning [ 19 ]. TTE is widely accepted as the primary screening tool in this setting, because it is noninvasive, convenient, and usually highly specific and sensitive [ 9 ].…”
Section: Discussionmentioning
confidence: 99%